PENINGKATAN KINERJA GURU MELALUI SUPERVISI KEPALA SEKOLAH DI SD INPRES BERTINGKAT MAMAJANG II KOTA MAKASSAR - Asmawati; Hamzah Upu; Andi Syukriani (STKIP Pembangunan Indonesia Makassar, 2021)
This study aims to 1) determine the impact of performance through the supervision of the principal, 2) find out the process of supervising the principal in improving teacher performance, 3) determine the performance of teachers after supervision is carried out. This research is a qualitative research conducted at the Mamajang II Inpres Elementary School with the research subjects being principals and teachers with the categories of senior teachers and junior teachers. Data was collected by using in-depth interviews, observation, and documentation techniques. The data analysis technique uses descriptive analysis techniques through data reduction, data display and data verification, while the validity of the data uses credibility, time triangulation, transperability, dependability, confirmability. The research results obtained are 1) the principal's supervision has an impact on improving teacher performance, including deviations in the implementation of learning so that improvement efforts are made, 2) the principal conducts academic supervision through class visits, meetings with teachers, discussions, class observations and private conversations, 3) teacher performance increased in the aspects of learning planning, implementation of learning and evaluation aspects after the supervision of the principal. Keywords: Teacher performance, supervision